Preparation method of light interpenetrating network short-time anti-oxidation high-temperature thermal insulation material
By designing an inorganic oxide layer on the carbon aerogel skeleton, the existing thermal protection materials have poor high temperature resistance and poor oxidation resistance under high temperature conditions, and the effects of low density, short-term oxidation resistance and high temperature insulation are achieved, and the thermal protection of hypersonic aircraft is suitable.
Patent Information
- Application Number
- CN202411710921.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-04
AI Technical Summary
Existing thermal protection materials have problems such as poor high temperature resistance and poor oxidation resistance under high temperature conditions, which is difficult to meet the strict requirements of hypersonic aircraft for thermal protection materials.
Carbon aerogel is used as the framework to design a layer of inorganic oxide on the surface of RF prepolymer. Through a specific preparation process, the advantages of inorganic oxide aerobic high temperature resistance and carbon aerogel's high temperature structure stability are complementary.
It improves the overall performance of the material, achieves low density, short-term anti-oxidation, and high-temperature heat insulation effects, and is suitable for the thermal protection field of hypersonic aircraft.
Smart Images

Figure CN119552327A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of high-temperature anti-oxidation thermal insulation materials, and specifically relates to a method for preparing a lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material. Background Art
[0002] During high-speed flight, a large amount of heat energy will be generated due to strong shock wave compression and viscous friction resistance, which will cause the aircraft's key hot end components such as the engine, nose cover, motor nozzle, and leading edge to face extremely severe thermal loads and anti-oxidation problems. Traditional thermal protection materials not only have disadvantages such as high density and high thermal conductivity, but also are prone to serious problems such as cracking, falling off, and even oxidation failure during use due to the difference in thermal expansion coefficient with the substrate. Therefore, lightweight insulation materials with certain high-temperature anti-oxidation properties are the focus of attention in the aviation field.
[0003] As a new type of nanoporous material, aerogel has extremely high specific surface area and porosity, as well as excellent thermal insulation performance, and is considered to be an ideal thermal insulation material. However, carbon materials have a commonality and disadvantage: in an oxygen-containing environment, when the temperature reaches about 400°C, oxidation reactions begin to occur, which greatly limits their stable application in extreme scenarios such as re-entry into the atmosphere. To overcome this problem, the literature [DOI.org / 10.1016 / j.corsci.2024.111944] uses argon oxygen plasma flame technology to generate a layer of ZrC-SiHfOC-MoSi2 coating on the surface of carbon / carbon (C / C) composite materials, which significantly improves the high-temperature oxidation resistance of the material. However, this type of method has a complex preparation process and high cost, which is not conducive to mass production. Therefore, it is particularly necessary to develop a new type of thermal protection material with a simple preparation process, low cost and certain antioxidant properties. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] The present invention proposes a method for preparing a lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material. Carbon aerogel is used as the skeleton, and a layer of inorganic oxide is designed on the surface of the RF prepolymer. Through a specific preparation process, the complementary advantages of the inorganic oxide's aerobic high-temperature resistance and the carbon aerogel's high-temperature structural stability are achieved, thereby improving the overall performance of the material, so as to solve the technical problems of poor high-temperature resistance and poor antioxidant performance in existing thermal protection materials, and to meet the stringent requirements of near-space hypersonic aircraft on the performance of thermal protection materials.
[0006] (II) Technical solution
[0007] In order to solve the above technical problems, the present invention proposes a method for preparing a lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material, the preparation method comprising the following steps:
[0008] S1. Resorcinol, formaldehyde, sodium carbonate and water are fully mixed in a certain proportion, placed in a constant temperature oven, and subjected to phenolic condensation reaction to prepare an RF prepolymer;
[0009] S2. Adding a certain proportion of an alcohol inhibitor to the RF prepolymer to obtain a pretreatment solution;
[0010] S3. Add a mixture of silane coupling agent and alcohol substances to the pretreatment solution, mix thoroughly and let it stand at room temperature to gel, and obtain a high-temperature thermal insulation material with a lightweight interpenetrating network and short-term antioxidant properties after aging, solution replacement, drying and high-temperature carbonization.
[0011] Furthermore, in step S1, the molar ratio of resorcinol to formaldehyde is 1:2, and the molar ratio of resorcinol to sodium carbonate is 300:1; in step S3, the molar ratio of resorcinol to silane coupling agent is (0.5-10):1.
[0012] Furthermore, in step S1, the mass fraction of resorcinol and formaldehyde in the total solution is 5-25%.
[0013] Furthermore, in step S2, the alcohol polymerization inhibitor includes one or more of ethanol, isopropanol or n-butanol, and the mass fraction of the alcohol polymerization inhibitor is 5-45%.
[0014] Furthermore, in step S3, the alcohol substance includes one or more of ethanol, isopropanol or n-butanol.
[0015] Furthermore, in step S3, the silane coupling agent includes one or more of KH550, KH602 or Si902, and the mass fraction of KH550 in the mixed solution of the silane coupling agent and the alcohol substance is 4-56%.
[0016] Furthermore, in step S1, the reaction temperature of the sodium carbonate-catalyzed reaction of resorcinol and formaldehyde is 25 to 45° C., and the reaction time is 10 to 24 hours.
[0017] Furthermore, in step S3, the aging temperature is 50°C, the aging time is 48-72h; the solvent is replaced with anhydrous ethanol for 5 times; the drying method is CO2 supercritical drying; high-temperature carbonization is carried out in a nitrogen atmosphere, the end temperature is 800-1050°C, and the temperature is kept constant for 2h.
[0018] (III) Beneficial effects
[0019] The invention provides a method for preparing a lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material. The method uses resorcinol, formaldehyde, KH550, alcohols and sodium carbonate solution as raw materials; firstly, a sodium carbonate aqueous solution is used to catalyze the reaction of resorcinol and formaldehyde to prepare an RF prepolymer; then, an alcohol substance is used as an inhibitor to control the molecular structure of the RF prepolymer, and further control the reaction rate of the RF prepolymer with KH550, so as to provide reaction conditions for obtaining a uniform and transparent interpenetrating network gel; finally, a mixed solution of KH550 and alcohol substances is added, and the gel is allowed to stand at room temperature, and after aging, solution replacement, drying and high-temperature carbonization, a lightweight interpenetrating network high-temperature thermal insulation nanomaterial is obtained. The lightweight interpenetrating network short-time antioxidant high-temperature thermal insulation material prepared by the method of the present invention uses carbon aerogel as the skeleton and designs a layer of inorganic oxide on the surface of the RF prepolymer. It has the characteristics of low density and short-time antioxidant, and can achieve the complementary advantages of aerobic high-temperature resistance of inorganic oxide and high-temperature structural stability of carbon aerogel, thereby improving the overall performance of the material. It is expected to be used as a short-time antioxidant high-temperature thermal insulation material in the thermal protection field of hypersonic aircraft.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention can effectively slow down the gelation speed and prolong the gelation time by introducing alcohol inhibitor / capping agent, thereby obtaining a homogeneous and transparent wet gel. The method of the present invention uses polymer design technology, has a simple preparation process and low cost, and can obtain a specific interpenetrating network composite material through design, and its density can reach 0.084g / cm 3 , the thermal conductivity at 1000℃ can reach 0.040W / (m·K). In addition, under high temperature conditions, the protective layer formed by sintering SiO2 can isolate the oxygen in the air to a certain extent, thereby preventing the composite material from further rapid oxidation. In an air atmosphere at 1000℃, the thermal weight loss in 5 minutes can reach 10.10%. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 SEM and mapping images of the high-temperature thermal insulation material prepared by the present invention;
[0023] Figure 2a N2 adsorption-desorption isotherms of the embodiments of the present invention and the comparative examples, Figure 2b is the pore size distribution curve;
[0024] Figure 3 The following are SEM images of composite materials with different components in the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0025] In order to make the purpose, content and advantages of the present invention more clear, the specific implementation methods of the present invention are further described in detail below in conjunction with the drawings and examples.
[0026] Example 1
[0027] S1. Dissolve 1.1 g of resorcinol in 13.58 g of water; after sufficient stirring, add 1.38 mL of formaldehyde solution and 0.85 mL of sodium carbonate solution (concentration of 4.17 g / cm 3 ); after magnetic stirring at room temperature for 30 minutes; the mixed solution was packaged into an ampoule bottle, placed in a 40°C oven for prepolymerization for 24 hours to perform a phenolic condensation reaction to obtain an RF prepolymer.
[0028] S2. Add 13 g of ethanol to the RF prepolymer and store at room temperature for later use.
[0029] S3. Take 0.590mL KH550 and dissolve it in 4g ethanol. After stirring, add it to the solution of step S2, stir quickly and let it gel at room temperature; then age at 50℃ for 72h, CO2 supercritical drying and carbonization at 900℃ for 2h to obtain a lightweight, short-term antioxidant high-temperature thermal insulation material.
[0030] Adding an alcohol inhibitor in step S2 can reduce the number of functional groups on the RF prepolymer molecules that react with KH550, thereby controlling the reaction rate with KH550 and preventing the RF prepolymer from further polymerizing to form a high molecule, thereby providing reaction conditions for obtaining a uniform and transparent interpenetrating network gel.
[0031] The lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material prepared in this embodiment has a density of 0.084 g / cm 3 ; The thermal conductivity at 1000℃ is 0.040W / (m·K); The thermal weight loss at 1000℃ in air atmosphere for 5 minutes is 13.33%.
[0032] Example 2
[0033] S1. Dissolve 1.1 g of resorcinol in 13.58 g of water; after sufficient stirring, add 1.38 mL of formaldehyde solution and 0.85 mL of sodium carbonate solution (concentration of 4.17 g / cm 3 ); after magnetic stirring at room temperature for 30 min; the mixed solution was packaged into an ampoule bottle, and placed in a 40° C. oven for prepolymerization for 24 h to form an RF prepolymer.
[0034] S2. Add 9 g of ethanol to the RF prepolymer and store at room temperature for later use.
[0035] S3. Take 0.235mL KH550 and dissolve it in 8g ethanol. After stirring, add it to the solution of step S2, stir quickly and let it gel at room temperature; then age at 50℃ for 72h, CO2 supercritical drying and carbonization at 900℃ for 2h to obtain a lightweight, short-term antioxidant high-temperature thermal insulation material.
[0036] The lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material prepared in this embodiment has a density of 0.120 g / cm 3 ; The thermal conductivity at 1000℃ is 0.055W / (m·K); The thermal weight loss at 1000℃ in air atmosphere for 5 minutes is 13.34%.
[0037] Example 3
[0038] S1. Dissolve 1.1 g of resorcinol in 13.58 g of water; after sufficient stirring, add 1.38 mL of formaldehyde solution and 0.85 mL of sodium carbonate solution (concentration of 4.17 g / cm 3 ); after magnetic stirring at room temperature for 30 min; the mixed solution was packaged into an ampoule bottle, and placed in a 40° C. oven for prepolymerization for 24 h to form an RF prepolymer.
[0039] S2. Add 13 g of ethanol to the RF prepolymer and store at room temperature for later use.
[0040] S3. Take 1.175mL KH550 and dissolve it in 4g ethanol. After stirring, add it to the solution of step S2, stir quickly and let it gel at room temperature; then age at 50℃ for 72h, CO2 supercritical drying and carbonization at 900℃ for 2h to obtain a lightweight, short-term antioxidant high-temperature thermal insulation material.
[0041] The lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material prepared in this embodiment has a density of 0.116 g / cm 3 ; The thermal conductivity at 1000℃ is 0.056W / (m·K); The thermal weight loss at 1000℃ in air atmosphere for 5 minutes is 10.10%.
[0042] Example 4
[0043] S1. Dissolve 1.1 g of resorcinol in 13.58 g of water; after sufficient stirring, add 1.38 mL of formaldehyde solution and 0.85 mL of sodium carbonate solution (concentration of 4.17 g / cm 3 ); after magnetic stirring at room temperature for 30 min; the mixed solution was packaged into an ampoule bottle, and placed in a 40° C. oven for prepolymerization for 24 h to form an RF prepolymer.
[0044] S2. Add 13 g of ethanol to the RF prepolymer and store at room temperature for later use.
[0045] S3. Take 4.695mL KH550 and dissolve it in 4g ethanol. After stirring, add it to the solution of step S2, stir quickly and let it gel at room temperature; then age at 50℃ for 72h, CO2 supercritical drying and carbonization at 900℃ for 2h to obtain a lightweight, short-term antioxidant high-temperature thermal insulation material.
[0046] The lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material prepared in this embodiment has a density of 0.165 g / cm 3 ; The thermal conductivity at 1000℃ is 0.098W / (m·K); The thermal weight loss at 1000℃ in air atmosphere for 5 minutes is 10.69%.
[0047] Comparative Example 1
[0048] The difference between this comparative example and Example 1 is that step S2 is omitted; in step S3, 0.590 mL of KH550 is dissolved in 17 g of ethanol (the total amount of ethanol in the whole system remains unchanged), stirred evenly, and then added to the solution in step 1. No gel can be obtained in this comparative example.
[0049] Comparative Example 2
[0050] The difference between this comparative example and Example 1 is that all the water in the system is replaced with ethanol of equal mass, and KH550 is used to directly catalyze the reaction of resorcinol and formaldehyde to form a gel. The specific operation is as follows:
[0051] S1. Dissolve 1.1 g of resorcinol in 13.58 g of ethanol; after thorough stirring, add 1.38 mL of formaldehyde solution.
[0052] S2. Take 0.590mL KH550 and dissolve it in 17g ethanol. After stirring, add it to the solution of step S1 and stir it magnetically at room temperature for 30 minutes. The mixed solution is encapsulated into an ampoule and placed at room temperature for gelation. Then, it is aged at 50°C for 72h, supercritical dried with CO2 and carbonized at 900°C for 2h to obtain a comparative material.
[0053] Refer to GB / T1463-2005 and use the geometric method to test the density of the material.
[0054] SEM scanning and BET test were used to characterize the microstructure of the obtained materials.
[0055] Table 1 Test results of various embodiments and comparative examples
[0056]
[0057]
[0058] It can be seen from the data in Table 1 that the lightweight interpenetrating network short-time antioxidant high-temperature thermal insulation material prepared by the method of the present invention has the characteristics of low density, high porosity, rich pore structure, etc.
[0059] After the composite material obtained by the present invention ablates carbon in air, the SiO2 aerogel can still maintain a block-shaped three-dimensional structure. Figure 1The uniform distribution of C and Si elements in the figure can illustrate that the present invention prepares a three-dimensional interpenetrating network structure material, which allows it to be used as a short-term anti-oxidation high-temperature thermal insulation material without problems such as cracking and falling off.
[0060] Figure 2a and 2b The N2 adsorption-desorption isotherms and pore size distribution curves of the embodiment of the present invention and the comparative example are shown in the figure: As can be seen from the figure, the composite material prepared in the embodiment has more micropores and mesoporous structures (compared with Figure 3 This is consistent with the SEM results in the literature), which is beneficial to reducing the gaseous thermal conductivity of the composite material.
[0061] Figure 3 The SEM images of the composite materials of different components in the embodiment of the present invention and the comparative example are shown in FIG. It can be seen that the three-dimensional network structure of the composite material and the size of the skeleton particles can be adjusted by controlling the amount of KH550 added in the embodiment. However, the three-dimensional structure obtained in the comparative example cannot be adjusted by controlling the amount of KH550 added.
[0062] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material, characterized in that: The preparation method comprises the following steps: S1. Resorcinol, formaldehyde, sodium carbonate and water are fully mixed in a certain proportion, placed in a constant temperature oven, and subjected to phenolic condensation reaction to prepare an RF prepolymer; S2. Adding a certain proportion of an alcohol inhibitor to the RF prepolymer to obtain a pretreatment solution; S3. Add a mixture of silane coupling agent and alcohol substances to the pretreatment solution, mix thoroughly and let it stand at room temperature to gel, and obtain a high-temperature thermal insulation material with a lightweight interpenetrating network and short-term antioxidant properties after aging, solution replacement, drying and high-temperature carbonization.
2. The method for preparing the lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material according to claim 1, characterized in that: In step S1, the molar ratio of resorcinol to formaldehyde is 1:2, and the molar ratio of resorcinol to sodium carbonate is 300:1; in step S3, the molar ratio of resorcinol to silane coupling agent is (0.5-10):
1.
3. The method for preparing the lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material according to claim 1, characterized in that: In step S1, the mass fraction of resorcinol and formaldehyde in the total solution is 5-25%.
4. The method for preparing the lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material according to claim 1, characterized in that: In step S2, the alcohol polymerization inhibitor includes one or more of ethanol, isopropanol or n-butanol, and the mass fraction of the alcohol polymerization inhibitor is 5-45%.
5. The method for preparing the lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material according to claim 1, characterized in that: In step S3, the alcohol substance includes one or more of ethanol, isopropanol or n-butanol.
6. The method for preparing the lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material according to claim 1, characterized in that: In step S3, the silane coupling agent includes one or more of KH550, KH602 or Si902, and the mass fraction of KH550 in the mixed solution of the silane coupling agent and the alcohol substance is 4-56%.
7. The method for preparing the lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material according to claim 1, characterized in that: In step S1, the reaction temperature of the sodium carbonate-catalyzed reaction of resorcinol and formaldehyde is 25 to 45° C., and the reaction time is 10 to 24 hours.
8. The method for preparing the lightweight interpenetrating network short-time anti-oxidation high-temperature thermal insulation material according to claim 1, characterized in that: In step S3, the aging temperature is 50°C, the aging time is 48 to 72 hours; the solvent is replaced with anhydrous ethanol for 5 times; the drying method is CO2 supercritical drying; high-temperature carbonization is carried out in a nitrogen atmosphere, the end temperature is 800 to 1050°C, and the temperature is kept constant for 2 hours.